x(x-4)=12

Apply the distributive property.

x⋅x+x⋅-4=12

Simplify the expression.

Multiply x by x.

x2+x⋅-4=12

Move -4 to the left of x.

x2-4x=12

x2-4x=12

x2-4x=12

Move 12 to the left side of the equation by subtracting it from both sides.

x2-4x-12=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -12 and whose sum is -4.

-6,2

Write the factored form using these integers.

(x-6)(x+2)=0

(x-6)(x+2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-6=0

x+2=0

Set the first factor equal to 0.

x-6=0

Add 6 to both sides of the equation.

x=6

x=6

Set the next factor equal to 0.

x+2=0

Subtract 2 from both sides of the equation.

x=-2

x=-2

The final solution is all the values that make (x-6)(x+2)=0 true.

x=6,-2

Solve Using the Square Root Property x(x-4)=12